The Improved Measurement of Building Thermal Transmittance in Zagreb Using a Temperature-Based Method - Igor Štambuk; Roman Malarić; Ivica Bakota; Zvonko Trzun (Sensors)
Theoretical U-values, which measure thermal transmittance, can be calculated based on the thermal parameters of an opaque element’s layers. However, practical measurements are essential to validate these theoretical values. The heat flux meter (HFM) method, is a widely accepted standard for such measurements. Despite its prevalence, the HFM method faces challenges, including wall surface roughness, ensuring proper contact between measurement devices and surfaces, and weather-related fluctuations. This study introduces a prototype system that employs a modified temperature-based method (TBM) to address these challenges. The paper provides a detailed comparison of thermal transmittance measurements obtained using both the modified TBM and the HFM method. The results showed U-value differences between the two methods. Additionally, these experimental findings were compared with theoretical calculations, highlighting the efficacy and potential of the modified TBM as an alternative approach for accurate U-value determination.